(untitled) (Fiep Bulletin - online, 2011)
Introduction: The stretch mark is skin atrophy, acquired due to disruption of elastic fibers in the second layer in dermis. These disruptions form parallel lesions and can affect both sexes, but the frequency is higher among females, being the main complaint among women. Objective: to compare through this research the treatment of stretch marks, between using STRIAT and acids, if there was some improvement in stretch marks visual appearance. Methodology: the study was longitudinal, through the exploratory method, qualitative, with a probability intentional sample. The sample was composed by four female patients from 21 to 26 years old. To collect data it was used photographic record and an evaluation form. Results: there was improvement in the atrophic stretch marks visual appearance in both techniques. But the treatment with acids had a significant improvement in the stretch marks continuity and length. Conclusion: the research is concluded by noting that after ten attendances there was improvement at stretch marks visual appearance, reduction in the their continuity and length, except for the patient 4 because of poor healing , addressing the research objective. As this is a new field, much remains to be explored searching new scientific evidences.